Sadullah el-Ankaravi : Daily concerns of an Ottoman Astrologer - Koç, Gülçin (Tunalı) (Thesis (M.A.) - Bogazici University. Institute of Social Sciences, 2002., 2002)
This thesis aims to study daily concerns of an Ottoman astrologer who lived in the first half of the 19th century in Ankara: Müderriszade Sadullah el-Ankaravi. Beside his prominent feature as an astrologer, he held the posts of naib, müftü and nakib-ül eşraf at different times. In addition to all of these, he was also a poet. His personal notes recorded at the edge of the calendars and horoscope collections were mainly analyzed in this study in order to understand the daily concerns of this multi-dimensional personality. Several other subjects like the places he lived in, his family, ilm-i nücum, his books, his education were considered to have a broader scope for the issue. Hence, the estate records and temettuat records about him were taken into consideration, either. This thesis does not belong to the genre of classical biography which was based on chronological order. Nevertheless, it has a particular type of narration which is tried to be emphasized throughout the thesis. For instance, an analogy between the daily concerns of Sadullah Efendi and his residence has been conducted in which his daily concerns has been narrated in the relevant rooms. Thus, it is aimed to approach the life of Sadullah Efendi as it was presented in his notes.
Keywords: Astronomy -- Turkey -- History.